Lipid-Lowering Therapy Utilization and Dosage Among Patients with Acute Coronary Syndrome Events: A Retrospective Cohort from 12 Community Hospitals - Khatib R; Yeh EJ; Glowacki N; McGuiness CB; Xie H; Wade RL; Kalich BA; Li Y; Rifai A; Sawlani N (Clinical Epidemiology, 2023)
Rasha Khatib,1 Eric J Yeh,2 Nicole Glowacki,1 Catherine B McGuiness,3 Handing Xie,4 Rolin L Wade,4 Bethany A Kalich,5 Yi Li,6 Abdelhadi Rifai,7 Neal Sawlani8 1Academic Research and Strategic Partnership, Advocate Aurora Research Institute, Advocate Aurora Health, Downers Grove, IL, USA; 2Global Health Economics and Outcomes Research (HEOR), Amgen Inc, Thousand Oaks, CA, USA; 3Health Economics and Outcomes Research, Real-World Evidence, IQVIA, Wayne, PA, USA; 4IQVIA, Wayne, PA, USA; 5Amgen Inc, Thousand Oaks, CA, USA; 6R&D Solutions, IQVIA, Bloomington, IL, USA; 7Heart & Vascular Institute, Cheyenne Regional Medical Group, Cheyenne, WY, USA; 8Advocate Lutheran General Hospital, Park Ridge, IL, USACorrespondence: Rasha Khatib, Academic Research and Strategic Partnership, Advocate Aurora Research Institute, Advocate Aurora Health, 3075 Highland Parkway, Suite 600, Downers Grove, IL, 60515, USA, Tel +1 708.684.3691, Email rasha.alkhatib@aah.orgIntroduction: Clinical practice guidelines recommend initiating a high-intensity LLT and continued monitoring of low-density lipoprotein cholesterol (LDL-C) following acute coronary syndrome (ACS). We used real-world data to describe LLT utilization after discharge and 1-year adherence. The reduction in LDL-C was also evaluated.Methods: Data were extracted from electronic health records (EHRs) from 12 hospitals in a large community healthcare system in midwestern United States between 2013 and 2019. Data on eligible patients recently discharged with an ACS event were linked to pharmacy claims data to describe LLT fill rates and 1-year post-discharge adherence. Adherence was reported as the proportion of days covered ≥ 80%.Results: Of the 10,589 eligible patients, 49% filled a high-intensity statin at discharge and only 36% were adherent at 1 year. The mean (SD) age was 66.1± 13.3, 39.3% were females, 58.8% were Caucasian, and 53.0% had Medicare. There was a clear trend for greater fill rates at discharge among patients with higher LDL-C values than those with lower values (p< 0.01). Key predictors of high-intensity (versus medium-intensity) LLT use within 21 days after an ACS event included ACS type (odds ratio [OR] 0.59; 95% confidence interval [CI] 0.52– 0.67 for NSTEMI versus STEMI), age group (OR: 0.59; 95% CI: 0.48– 0.72 for > 75 years versus < 65 years), and statin use before index ACS event (OR: 1.56; 95% CI: 1.23– 1.88).Conclusion: This real-world study found that despite recommendations in clinical practice guidelines, high-intensity LLT fill rates at discharge and 1-year adherence to LLT remain suboptimal. Clinical characteristics, including ACS type and LDL-C values, were strong predictors of filling and adherence to guideline-recommended therapy. Age, sex, and race/ethnicity disparities were observed in discharge fill rates and 1-year adherence. These results highlight the need for continued efforts at the patient and provider levels to improve LLT adherence among ACS patients.Keywords: lipid-lowering therapy, high-intensity statin, acute coronary syndrome, real-world data, prescribing, adherence